Metadiscourse In Covid-19 Vaccine Opinion Articles: A Contrastive Study Between American And Malaysian English-Language Online Newspapers - Angelina Nicollina, Felix Hospi (Universiti Malaysia Sarawak (UNIMAS), 2020)
This paper seeks to explore the use of metadiscourse markers in COVID-19 vaccine opinion articles in American and Malaysian online newspapers. The objectives in this study include (1) to identify the metadiscourse categories and sub-categories used in Malaysian and American online newspapers in COVID-19 vaccine opinion articles, (2) to investigate the frequency of interactive and interactional metadiscourse markers in these two texts, (3) to analyse how interactive and interactional metadiscourse markers are used to achieve persuasion in the two texts, and (4) to investigate if there is any significant relationship between the distribution and use of interactive and interactional metadiscourse in these texts. In this study, descriptive research design with both qualitative and quantitative approach is used. The research framework used in this study is Hyland’s (2005) taxonomy of metadiscourse. The findings of this study reveal that both interactive and interactional metadiscourse are present in American and Malaysian COVID-19 vaccine opinion articles. However, there are similarities and differences in the way American and Malaysian writers employ these markers in the writing of COVID-19 vaccine opinion articles.